Development of Ethnophysics-Based Augmented Reality Assisted Digital Teaching Material for 21st Century Learning - Febrian Virijai; Asrizal Asrizal (Postgraduate, University of Mataram, 2023)
Twenty-first century learning includes 21st century skills, but the facts show that students' 21st century skills are still low. The solution to this problem is to develop digital teaching materials integrated with AR and ethnophysics. The purpose of this study was to determine the initial study, validity, and practicality of using ethnophysics-integrated digital AR teaching materials. The research method used is development research with the Plomp model. The research instruments used include needs analysis instruments, validation questionnaires and practicality. The data analysis technique used is descriptive statistics. Based on the data that has been analyzed there are three research results. First, the results of the needs analysis obtained an average value of 63 with a good enough category. Second, product validation results obtained an average value of 90.5 with a very good category. Third, the product practicality results obtained an average value of 89.9 in the very good category. The implication of the research results is that teachers can construct student skills through digital teaching materials. The results of this study concluded that ethnophysics-based AR-assisted digital teaching materials are valid and practical for use in learning